Conversion of lignin with polystyrene into high-value aromatics through co-pyrolysis and post-plasma refining - Fan, Yongsheng; Qin, Changsheng; Zhao, Keyu; Xiong, Yonglian; Shi, Yunxi (Energy (Oxford), 2025)
Lignin was co-pyrolyzed with polystyrene to subject volatiles to post-plasma refining for potential aromatic production, mainly focusing on effects of blend ratio and plasma parameters. Firstly, the co-pyrolysis at equal mass ratio was beneficial for reducing residual char and reaction energy barrier. Secondly, elevating polystyrene blend ratio could improve oil yield, fuel-grade, and aromatic selectivity, but the improvement was compromised, showing volatiles synergy and plasma excitation were more favorable at a balanced ratio, because the H-donation of polystyrene and the bond-cleavage ability of lignin-derived oxyradicals were fully utilized. Thirdly, increasing plasma current enhanced plasma emission spectra, meaning more energetic reactive species, while extending discharge length had a little effect on the spectra, but doubling the discharge length had a more obvious refining effect than increasing the discharge current by equal steps. Fourthly, increased plasma parameters contributed to the breakage of bridged bonds between benzene rings and the loss of aliphatic side-chains, deepening deoxygenation, lowing molecular weight, and raising aromatic proton ratio. However, higher plasma current mainly weakened the selectivity of monocyclic aromatics, and higher discharge length severely decreased the aromatic yield. Therefore, this study suggested the possibility of using non-catalytic methods to recover high-value aromatics from lignin and polystyrene. [Display omitted] •A novel integrated co-pyrolysis and post-plasma refining system was developed.•Co-pyrolysis at equal mass ratio reduced char content and reaction energy barrier.•Synergy of volatiles and plasma promotion were more favorable at equal blend ratio.•Higher current weakened MAHs selectivity and longer duration severely reduced yield.•Plasma refining gave a new route for lignin and polystyrene conversion into aromatics.